PENGARUH SERTIFIKASI GURU TERHADAP KINERJA GURU DI SD NEGERI 091277 SIANTAR ESTATE - Simanjuntak, Melvin; Giana Putri; Fidya Ayu Ningsih; Yensiska R Siburian; Juliana Matondang; Bthalia Margaretha Siburian; Duma Turnip; Sabar Mangatur Sirait (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to find out and explain how teacher certification influences teacher performance in state elementary schools. 091277 Siantar Estate. The research method used is a quantitative method. The population taken in this research were 6 certified teachers and the sample was the entire population. Apart from having competency, teachers are also required to have standard academic qualifications, an educator certificate, be physically and spiritually healthy, and have the ability to realize educational goals in Indonesia. teacher, while an educator certificate is formal proof of recognition given to teachers as professionals. Having an educator certificate is one way in the world of education to improve the quality and professionalism of a teacher, so that in the future all teachers must have an educator certificate as a license or teaching letter. The results of this research show the influence of certification in teaching and being able to carry out their duties well.